Various Deep Learning Methods for Hyperspectral Images - Sivaram M.; Shobana S.J.; Khan M.; Ramakrishnan J.; Goel P.M.; Maseleno A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Image processing; Learning systems; Remote sensing; Spectroscopy; Hyper-spectral imageries; Image processing technique; Learning methods; Learning process; Learning techniques; Models of learning; Remote sensing applications; Spectral channels; Deep learning